1987
DOI: 10.1139/v87-065
|View full text |Cite
|
Sign up to set email alerts
|

The temperature dependence of the Raman spectrum and gauche interactions of tri-N-butylamine: a conformational study

Abstract: M. S. LAMPREIA. Can. J . Chem. 65, 384 (1987).Raman spectra of tri-n-butylamine show pairs of bands whose temperature-dependent intensities clearly suggest their assignment to different conformers in simultaneous equilibria. These spectroscopic data are interpreted and correlated with structural information obtained from statistical analysis of gauche skeletal arrangements in tri-n-butylamine. The average numbers of gauche interactions in various tri-n-alkylamines are used to evaluate partial molal volumes whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…23 Fundamental Raman modes of the BA cation fall in the R2 range (1200−1800 cm −1 ), which comprises the angular distortion of CH 2 , CH 3 , and NH 2 groups. 32,33 The observed Raman modes in our experiments in the R2 range at ≈1251 cm −1 correspond to CH 2 twisting, ≈1300 cm −1 to CH 2 wagging, ≈1458 cm −1 to a mixture of CH 2 scissoring vibration and CH 3 antisymmetric deformation, ≈1556 cm −1 to asymmetric NH 3 deformation, and ≈1584 cm −1 to NH 3 + degenerate deformation, while the mode at ≈1323 cm −1 marked with a blue asterisk is not reported in the literature (Figure S7). 23,29,32,33 A plausible explanation for the 1323 cm −1 mode could be that a strong interaction between BA and MA molecules of RP2 on gold with incoming photons has led to the splitting of mode at ≈ 1320 cm −1 into 1300 and 1323 cm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Fundamental Raman modes of the BA cation fall in the R2 range (1200−1800 cm −1 ), which comprises the angular distortion of CH 2 , CH 3 , and NH 2 groups. 32,33 The observed Raman modes in our experiments in the R2 range at ≈1251 cm −1 correspond to CH 2 twisting, ≈1300 cm −1 to CH 2 wagging, ≈1458 cm −1 to a mixture of CH 2 scissoring vibration and CH 3 antisymmetric deformation, ≈1556 cm −1 to asymmetric NH 3 deformation, and ≈1584 cm −1 to NH 3 + degenerate deformation, while the mode at ≈1323 cm −1 marked with a blue asterisk is not reported in the literature (Figure S7). 23,29,32,33 A plausible explanation for the 1323 cm −1 mode could be that a strong interaction between BA and MA molecules of RP2 on gold with incoming photons has led to the splitting of mode at ≈ 1320 cm −1 into 1300 and 1323 cm.…”
Section: Resultsmentioning
confidence: 99%
“…32,33 The observed Raman modes in our experiments in the R2 range at ≈1251 cm −1 correspond to CH 2 twisting, ≈1300 cm −1 to CH 2 wagging, ≈1458 cm −1 to a mixture of CH 2 scissoring vibration and CH 3 antisymmetric deformation, ≈1556 cm −1 to asymmetric NH 3 deformation, and ≈1584 cm −1 to NH 3 + degenerate deformation, while the mode at ≈1323 cm −1 marked with a blue asterisk is not reported in the literature (Figure S7). 23,29,32,33 A plausible explanation for the 1323 cm −1 mode could be that a strong interaction between BA and MA molecules of RP2 on gold with incoming photons has led to the splitting of mode at ≈ 1320 cm −1 into 1300 and 1323 cm. −134 This further emphasizes that the enhanced light− matter interaction leads to an increase in the intensity of the nominally weak Raman modes of HOIP crystals in addition to the observation of hitherto unknown and unseen modes.…”
Section: Resultsmentioning
confidence: 99%
“…In the experimental context, spectroscopic techniques with an emphasis on Raman spectroscopy, crystallography and microwave spectroscopy are the most used techniques to analyze the probable conformations of molecules of interest and then determine the values of rotational barriers [ 11 , 12 , 13 ]. On the other hand, computational studies have been frequently found in the literature, looking for elucidate the stereoelectronic effects responsible for the most stable conformations of different systems [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%